The Role Played by Mitochondria in FcεRI-Dependent Mast Cell Activation - Chelombitko, Maria A.; Chernyak, Boris V.; Fedorov, Artem V.; Zinovkin, Roman A.; Razin, Ehud; Paruchuru, Lakhsmi Bhargavi (Frontiers in Immunology, 2020)
Mast cells play a key role in the regulation of innate and adaptive immunity and are involved in pathogenesis of many inflammatory and allergic diseases. The most studied mechanism of mast cell activation is mediated by the interaction of antigens with immunoglobulin E (IgE) and a subsequent binding with the high-affinity receptor FcεRI. Increasing evidences indicated that mitochondria are actively involved in the FcεRI-dependent activation of this type of cells. Here, we discuss changes in energy metabolism and mitochondrial dynamics during IgE-antigen stimulation of mast cells. We reviewed recent data with regards to the role played by mitochondrial membrane potential, mitochondrial Ca2+ influx and reactive oxygen species (ROS) in mast cell FcεRI-dependent activation. Additionally, in the present review we discuss the crucial role played by the transcription factors STAT3 and MITF in the development and function of mast cells. These two transcription factors resides in the mitochondria and functions as direct modulators of mitochondrial activity. Studying the role played by mast cell mitochondria following their activation is essential for expanding our basic knowledge about mast cell physiological functions and would help to design mitochondria-targeted anti-allergic and anti-inflammatory drugs.